2020
DOI: 10.1159/000509370
|View full text |Cite
|
Sign up to set email alerts
|

Retronychia: A Paradigm Shift?

Abstract: Retronychia is an increasingly known cause of paronychia. It was classically regarded as an indication for total nail plate avulsion, but recent case series have questioned the real need for this approach. In order to establish a proper recommendation for patients presenting with retronychia, we retrospectively reviewed all articles with retronychia case reports. Total nail plate avulsion is still the most efficient treatment option. Topical steroids and other noninvasive approaches can be useful in some early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…[1][2][3] Two recent review articles have shown that surgical avulsion of the nail plate produces the highest cure rate, with reported resolution of the process in 78% and 96% of patients. 2,4 Despite the demonstrated clinical efficacy of surgical nail avulsion, long-term sequelae are reported in approximately 1 of every 10 patients undergoing surgical intervention, with complications including the development of nail dystrophy because of problems with the underlying nail bed and/or distal matrix, pain, distal embedding, nail splitting, ingrown nail formation, and scarring. 2 To preserve the anatomic location between PNF and the nail matrix, the most adherent nail may be left in place when it is healthy; however, this can be challenging to accomplish because of the typically shortened state of this nail, the fact that the innermost nail may also be unhealthy, and the difficulty of removing overlying nails without avulsing the most adherent nail.…”
Section: Nature Of the Conundrummentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Two recent review articles have shown that surgical avulsion of the nail plate produces the highest cure rate, with reported resolution of the process in 78% and 96% of patients. 2,4 Despite the demonstrated clinical efficacy of surgical nail avulsion, long-term sequelae are reported in approximately 1 of every 10 patients undergoing surgical intervention, with complications including the development of nail dystrophy because of problems with the underlying nail bed and/or distal matrix, pain, distal embedding, nail splitting, ingrown nail formation, and scarring. 2 To preserve the anatomic location between PNF and the nail matrix, the most adherent nail may be left in place when it is healthy; however, this can be challenging to accomplish because of the typically shortened state of this nail, the fact that the innermost nail may also be unhealthy, and the difficulty of removing overlying nails without avulsing the most adherent nail.…”
Section: Nature Of the Conundrummentioning
confidence: 99%
“…Furthermore, the use of an autologous nail plate avoids introducing foreign material into the nail unit and subsequent dermatologic complications, most notably infection and scarring. [2][3][4][5] We propose that the autologous nail plate should be considered as the preferred option for placeholder material when performing complete nail avulsion for retronychia. We present this case of nail unit reconstruction using the autologous nail plate after complete nail avulsion and excision of excessive granulation tissue performed to treat severe retronychia to demonstrate the long-term benefits of this procedure in achieving a functional nail unit.…”
Section: Conundrum Resolutionmentioning
confidence: 99%
“…Als definitive und von den teils erheblichen Schmerzen befreiende Therapie hatte sich zunächst die schonende Avulsion der Nagelplatte etabliert [62,63]. Inzwischen gibt es Erfahrungen mit der topischen und intraläsionalen Behandlung mit Steroiden, die in frühen Stadien helfen können, operative Maßnahmen zu vermeiden [64][65][66].…”
Section: Retronychieunclassified